DTI parameters in neonates with hypoxic-ischemic encephalopathy after total body hypothermia. (2nd November 2022) - Longo, D.; Bottino, F.; Lucignani, G.; Scarciolla, L.; Pasquini, L.; Rossi Espagnet, M. C.; Polito, C.; Figà-Talamanca, L.; Calbi, G.; Savarese, I.; Giliberti, P.; Napolitano, A.
Abstract: Background and purpose: MR imaging provides means for discriminating different patterns of Hypoxic-ischemic encephalopathy (HIE) and may distinguish most severe cases from less severe but is unable to predict long-term outcome. Diffusion tensor imaging (DTI) offers information for a more complete characterization of HIE. The purpose of this study is to compare the modifications of DTI parameters in newborns one week and six months following total-body cooling to healthy controls. Methods: Forty-seven cooled newborns were studied with MRI, 20 underwent follow-up at 6 months. 12 healthy newborns and nine children at 6 months were enrolled as control groups (HC). Inferior Longitudinal Fasciculus (ILF), Corpus Callosum Fasciculus (CCF), Corticospinal Tract (CST), Optical Tract (OT), Optic Radiation (OR) were generated in all subjects. DTI parameters were evaluated in basal ganglia (BG), thalamus (TH) and tracks. Statistical analysis was performed with MANOVA. Results: In newborns HIE versus HC, there were significantly lower fractional anisotropy (FA) on OR and CST and higher axial diffusivity (AD), apparent diffusion coefficient (ADC) and radial diffusivity (RD) values on CST, BG and TH in HIE-N. At 6 months there were no significant grouping effects. The analysis showed a significant increase of FA, decrease of ADC, AD, RD after 6 months for HIE and HC. Conclusions: We observed modifications of parameter values in HIE newborns vs HC; however normalization of values at 6 months suggests that changes of parameters cannot be considered early biomarkers for evaluation of therapeutic hypothermia in newborns with moderate HIE and normal conventional MRI.